Development of GPS-Based Mobile Application for Motorized Vehicle Speed Survey - Winarno Sugeng; Theta Dinnarwaty Putri; Hanif Al Kamal (BBPSDMP KOMINFO MAKASSAR, 2019)
The problem of measuring vehicle speed on roads is difficult to be one of the problems in the Department of Transportation. Through this research, alternative methods of measurement on road segments proposed by using GPS through vehicle speed calculations are measured based on latitude and longitude displacement applied to mobile applications.The method used to calculate vehicle speed is using the method of calculating the distance between Euclidean Distance coordinates, the acquisition of the speed results is then used to determine the determination of the congestion status. The result of distance calculation is still in units of degree, therefore it is necessary to convert from coordinate unit (degree) to unit distance (km) by multiplying the distance of one degree of earth based on latitude. Based on the test results, there are three phases when taking measurements: pre-measurement, measurement, and post-measurement.